We have to solve 3 l x-3 l + 4 = 10.

3 l x-3 l + 4 = 10

=> 3* |x - 3| = 6

=> | x -3 | = 2

This equation is satisfied for the following cases:

x - 3 = 2

=> x = 5

and 3 - x = 2

=> x = 1

**Therefore x is equal to 5 and 1.**

3 l x-3 l + 4 = 10

To solve for x , we need to isolate the absolute value on the left side.

First we will subtract 4 from both sides.

==> 3 l x-3 l = 6

Now we will divide by 3.

==> l x-3 l = 2

Now we have two cases.

Case(1): Positive value.

==> x-3 = 2 ==> x = 5

Case(2) : negative value.

==> -(x-3) = 2 ==> -x + 3 = 2 ==> -x = -1 ==> x = 1

==> Then the values of x are :

**x = { 1, 5}**